UM ARCABOUÇO PARA DETECÇÃO E ALERTA DE ANOMALIAS DE MOBILIDADE URBANA EM TEMPO REAL - Thome, Marco Aurelio Brunoro (2020)
Data gathered by sensors, cameras, social networks, and applications can contribute on automatic detection of atypical traffic events like accidents and floodings. Moreover, the heterogeneous nature of a plethora of data sources has the advantage of infor